Overview the reading comprehension capability elementary students in Banten Province of Indonesia - Lestari, Mas Roro Diah Wahyu; Sumantri, Muhammad Syarif; Supena, Asep (International Journal for Educational and Vocational Studies, 2022)
Banten Province is a province adjacent to the Capital of Indonesia, Jakarta. Many workers in Jakarta live in Banten Province. The high mobility of Banten workers working in Jakarta caused the outbreak of the Covid virus which is quite high in Banten. The focus of this research area is on one of the areas in Banten province, namely Tangerang and South Tangerang, which is the border area between Jakarta and Banten. For almost two years Covid, Tangerang and south Tangerang faced an increase in poverty rates and decreased quality of school-age human resources The increase in poverty affects students' ability to understand reading due to low purchasing power of children's reading books. The impact of reading comprehension skills in 5th graders is the focus of research. Inability to understand reading in children can affect regional and state development. This research aims to identify the competence of reading comprehension skills in elementary school children in Banten province. This study uses descriptive quantitative research using random sampling in 5th graders spread across two cities in Banten province. Data collection was done using tests in 5th graders as many as 110 participants. Data processing is carried out using average or mean on 3 cognitive reading comprehension abilities which are then displayed in graphic form. The results showed that there was a decrease in reading comprehension ability in 8 reading comprehension competencies. The average result of the value of the ability to understand reading in Banten province is 62. This research report provides input to local and central governments to address the decline in students' reading comprehension skills. The decline in household income in Banten has an influence on the decline in reading comprehension ability.